Brand Equity and Purchase Decisions on French Fries Product in Indonesia - Mentari, Junifer; Ghandy, Abel; Tua Manalu, Doni Sahat; Hardini, Sri Y.K (Jurnal Organisasi dan Manajemen, 2020)
This study aims to determine the effect of brand awareness, brand associations, perceived quality, and brand loyalty to purchase decisions of French Fries. The research is quantitative and the sampling technique is purposive sampling, with 100 respondents. The researcher applies multiple regression analysis as data analysis techniques. Findings. The results show that all brand equity variables affect to purchasing decision of French fries. To improve brand awareness, corporate needs to advertise products on television and social media such as Instagram or food platforms. For brand association improvement, producers need to create new French Fries flavor. Attractive packaging design and usage instructions for perceived quality improvement. In brand loyalty must maintain consistency of product taste.